Managing antibiotics wisely: a quality improvement programme in a tertiary neonatal unit in the UK. Issue 2 (7th May 2018) - Makri, Vasiliki; Davies, Gemma; Cannell, Stephanie; Willson, Katherine; Winterson, Lucy; Webb, Joanna; Kandhari, Amit; Mansour, Maha; Thomas, Joanne; Morris, Geraint; Matthes, Jean; Banerjee, Sujoy
Abstract : Microbial resistance to antibiotics is a serious global health problem compounded by antibiotic overuse and limited investment in new antibiotic research. Inappropriate perinatal antibiotic exposure is increasingly linked to lifelong adverse outcomes through its impact on the developing microbiome. Antibiotic stewardship may be the only effective preventative strategy currently available. As the first tertiary neonatal unit in the UK to collaborate in an international quality improvement programme (QIP) with Vermont Oxford Network (VON), we present the results of our antibiotic stewardship initiative. The QIP was officially launched in January 2016 and aimed to reduce antibiotic usage rate (AUR) by 20% of baseline by 31st December 2016 without compromising patient safety. A multidisciplinary team of professionals and parent representatives shared good practices and improvement strategies through international webinars and local meetings, devised uniform data collection methodology and implemented a number of carefully selected 'Plan–Do–Study–Act' cycles. Run charts were used to present data and, where appropriate, statistical analysis undertaken to compare outcomes. The QIP resulted in a sustained reduction in AUR from a baseline median of 347 to 198 per 1000 patient-days (a reduction of 43%). The proportion of culture-negative sepsis screens where antibiotics were stopped within 36–48 hours increased consistently from a baseline of 32.5% to 91%. The antibiotic days per patient at discharge reduced from a median of 3 to 2 days, and there was a reduction in practice variation. Our annual mortality and necrotising enterocolitis rates for the VON cohort (<30 weeks or <1500 g) were the best ever recorded, 5.5% and 1.4%, respectively. Audits confirmed a high level of staff and family awareness of the QIP. The QIP achieved a sustained reduction in antibiotic use without compromising patient safety. Our challenge is to sustain this improvement safely.